XBB.1.5 monovalent mRNA vaccine booster elicits robust neutralizing antibodies against XBB subvariants and JN.1 - Wang, Qian; Guo, Yicheng; Bowen, Anthony; Mellis, Ian A.; Valdez, Riccardo; Gherasim, Carmen; Gordon, Aubree; Liu, Lihong; Ho, David D. (Cell host & microbe, 2024)
COVID-19 vaccines have recently been updated to specifically encode or contain the spike protein of the SARS-CoV-2 XBB.1.5 subvariant, but their immunogenicity in humans has yet to be fully evaluated and reported, particularly against emergent viruses that are rapidly expanding. We now report that administration of an updated monovalent mRNA vaccine booster (XBB.1.5 MV) to previously uninfected individuals boosted serum virus-neutralizing antibodies significantly against not only XBB.1.5 (27.0-fold increase) and EG.5.1 (27.6-fold increase) but also key emerging viruses such as HV.1, HK.3, JD.1.1, and JN.1 (13.3- to 27.4-fold increase). Individuals previously infected by an Omicron subvariant had the highest overall serum neutralizing titers (ID50 1,504–22,978) against all viral variants tested. While immunological imprinting was still evident with the updated vaccines, it was not nearly as severe as observed with the previously authorized bivalent BA.5 vaccine. Our findings strongly support the official recommendation to widely apply the updated COVID-19 vaccines. [Display omitted] •An XBB.1.5 booster markedly enhanced neutralization of SARS-CoV-2, including JN.1•An XBB.1.5 booster induced similar antibody titers to XBB infection•Omicron infection followed by XBB.1.5 booster yielded the highest antibody titers•Our findings supported recommendations for broad use of the updated XBB.1.5 booster Wang et al. observed that administration of the updated COVID-19 vaccine booster targeting XBB.1.5 significantly increased neutralizing antibody responses against the most prevalent and emerging SARS-CoV-2 variants, including JN.1. This result was observed in both uninfected individuals and those with prior Omicron infection, supporting recommendations for its widespread use.